Effects of Light Intensity and Seedling Mediaon The Growth of Reutealis Trisperma (Blanco) Airy Shaw Seedling - Wardiana, Edi; Herman, Maman (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2011)
This experiment was conducted at Pakuwon Experimental Station with altitude about 450 m above sea level and Latosol type of soil beginning from January until June 2009. It aimed to investigate the effect of light intensity and seedling media on growth of